Transformative Pedagogic Practice Education for Sustainable Development and Water Conflicts in Indian Geography Education - Leder, Stephanie (Education for Sustainability,, 2018)
This book explores how the transnational Education for Sustainable Development (ESD) policy is being translated into formal school education in India. Stephanie Leder investigates the ESD's transformative potential for pedagogic practice and builds a set of principles for how the global objectives of the ESD can be interpreted in diverse socio-cultural contexts. Her approach for transformative pedagogic practice emphasizes the promotion of a critical consciousness through argumentation skills. Using the case of water conflicts in geography education in India, the book reveals the contradictions between ESD objectives and curricula, syllabi, textbooks and classroom teaching at secondary schools in Pune, Maharashtra. Leder's approach demonstrates how principles of schooling can be altered towards learner-centered, problem-posing and network-thinking teaching approaches to empower students towards reflective decision-making on the sustainable use of natural resources.